PENGARUH MANAJEMEN LABA, PERTUMBUHAN ASET DAN TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Aneka Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Saragih, Muhammad Rizal; Rusdi, Rusdi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research investigates the influence of earnings management, asset growth, and tax avoidance on firm value. In the contemporary business environment, companies employ various strategies to enhance financial performance and market valuation. Earnings management practices, asset expansion, and tax planning have emerged as critical factors affecting the overall value of a firm. Understanding the interplay of these elements is essential for stakeholders, regulators, and investors seeking to make informed decisions in the dynamic landscape of corporate finance. The primary objectives of this study are to examine the individual and collective effects of earnings management, asset growth, and tax avoidance on firm value. By analyzing the relationships between these variables, the research aims to contribute valuable insights into the intricate dynamics shaping corporate financial outcomes. The population of this study are Multi-Industry Companies Listed on the Indonesia Stock Exchange in 2016-2020. The sample of this research is 46 companies. The results of this study are earnings management, asset growth, and tax avoidance have an effect on firm value. The research suggests that understanding and considering the interactions between earnings management, asset growth, and tax avoidance is crucial for comprehending how these financial strategies impact the overall value of a company in the business and investment landscape.